Sosialisasi Pencatatan Keuangan pada UMKM Fried Chicken Lazatto di Tigaraksa, Tangerang - Nugroho, Ibrahim Tri; Ahmad Rasyiddin; Febri Sari Siahaan (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
Effective financial recording is a crucial element in managing micro, small and medium enterprises (MSMEs), especially in the context of the fast food industry. This journal examines approaches to socialization and implementation of simple bookkeeping to improve financial recording at Fried Chicken Lazatto MSMEs in Tigaraksa. The method used includes direct training to MSME owners regarding the importance of regular and accurate financial records. The research results show that implementing a simple recording system can improve understanding of cash flow, expenses and daily income. Thus, this journal offers recommendations for the use of financial recording systems that can be adopted by similar MSMEs, promoting the benefits of effective bookkeeping practices in improving the performance and sustainability of MSMEs in the food sector.